Surface/Interface Engineering for High-Resolution Micro-/Nano-Photodetectors - Chang, Jinlin; Liu, Ting; Geng, Xiao; Dai, Genting; Yang, Liangliang; Cheng, Mingjun; Jiang, Linpan; Sun, Zhenyuan; Liu, Jianshe; Chen, Wei (Nano-Micro Letters, 2026)
Photodetectors can convert light energy into electrical signals, so are widely used in photovoltaics, photon counting, monitoring, and imaging. Photodetectors are easy to prepare high-resolution photochips because of their small size unit integration. However, these photodetector units often exhibit poor photoelectric performance due to material defects and inadequate structures, which greatly limit the functions of devices. Designing modification strategies and micro-/nanostructures can compensate for defects, adjust the bandgap, and develop novel quantum structures, which consequently optimize photovoltaic units and revolutionize optoelectronic devices. Here, this paper aims to comprehensively elaborate on the surface/interface engineering scheme of micro-/nano-photodetectors. It starts from the fundamentals of photodetectors, such as principles, types, and parameters, and describes the influence of material selection, manufacturing techniques, and post-processing. Then, we analyse in detail the great influence of surface/interface engineering on the performance of photovoltaic devices, including surface/interface modification and micro-/nanostructural design. Finally, the applications and prospects of optoelectronic devices in various fields such as miniaturization of electronic devices, robotics, and human–computer interaction are shown. Highlights: 1 Surface/interface engineering can compensate for defects, adjust the bandgap, and develop novel quantum structures, which consequently optimize photovoltaic units and revolutionize optoelectronic devices. 2 This review comprehensively elaborates on the surface/interface engineering scheme of micro-/nano-photodetectors from principles, types, and parameters, and describes the influence of material selection and manufacturing techniques. 3 Surface/interface engineering continuously promotes the development of low-dimensional optoelectronic materials and drives the industrialization of flexible optoelectronic devices.